OBSTRUCTIVE SLEEP APNEA-HYPOPNEA SYNDROME. MODERN VIEW ON THE PROBLEM - Fomych, G .M.; Celyk, N. E.; Petrenko, O. E.; Pogoreckiy, U. N.; Anyasi, I. Ch. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
Obstructive sleep apnea syndrome is a common chronic syndrome that significantly affects the quality of life of patients and often requires lifelong care. This review deals with modern ideas about the prevalence, causes, clinical presentation, diagnosis and treatment of obstructive sleep apnea syndrome. Using modern methods of diagnosis and the correct approach to such patients helps prevent unwanted effects and significantly improves quality of life.